Proceedings of the Ninth ACM International Conference on Interactive Tabletops and Surfaces 2014
DOI: 10.1145/2669485.2669496
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Situation Awareness in Collaborative Tabletop Systems with Automation

Abstract: Human operators collaborating to complete complex tasks, such as a team of emergency response operators, need to maintain a high level of situation awareness to appropriately and quickly respond to critical changes. Even though automation can help manage complex tasks and rapidly update information, it may create confusion that negatively impacts operators' situation awareness, and result in suboptimal decisions. To improve situation awareness in colocated environments on digital tabletop computers, we develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In this section, we first summarize the quantitative results from Phase 1 on the control placement and feedback location factors (details can be found in our previous publication [3]) to motivate our video analysis. Next, we present our video analysis results on timeline configurations and describe how timelines and other system features were used for the three levels of situation awareness.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section, we first summarize the quantitative results from Phase 1 on the control placement and feedback location factors (details can be found in our previous publication [3]) to motivate our video analysis. Next, we present our video analysis results on timeline configurations and describe how timelines and other system features were used for the three levels of situation awareness.…”
Section: Resultsmentioning
confidence: 99%
“…The results from a detailed analysis of Phase 1, previously published in Chang et al [3], revealed that replicated timelines -where each player had their own copy in their personal space -encouraged more timeline interactions. More interactions with the timeline correlated with higher levels of individual situation awareness.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations